2007
DOI: 10.1248/bpb.30.2402
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone 5.ALPHA.-Reductase Inhibitory Active Constituents of Piper nigrum Leaf

Abstract: dition, the P. nigrum leaf extract showed in vivo anti-androgenic activity using the hair regrowth assay in testosterone sensitive male C57Black/6CrSlc strain mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 19 publications
1
22
1
1
Order By: Relevance
“…Two major lignans of PN-ext, (Ϫ)-cubebin (1) and (Ϫ)-3,4-dimethoxy-3,4-desmethylenedioxycubebin (2), were already isolated from the ethyl acetate soluble fraction as described in the previous paper. 1,4) Because Tsuruga et al 15) reported that several cubebin-type lignans having 3,4-dibenzyltetrahydrofuran ring, such as matairesinol and trachelogenin, had significant histamine release inhibitory activities, we examined inhibitory effects of 1 and 2 on compound 48/80-induced histamine release from rat peritoneal mast cells. As shown in Table 3, the inhibitory activities of 1 and 2 were superior to that of SCG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two major lignans of PN-ext, (Ϫ)-cubebin (1) and (Ϫ)-3,4-dimethoxy-3,4-desmethylenedioxycubebin (2), were already isolated from the ethyl acetate soluble fraction as described in the previous paper. 1,4) Because Tsuruga et al 15) reported that several cubebin-type lignans having 3,4-dibenzyltetrahydrofuran ring, such as matairesinol and trachelogenin, had significant histamine release inhibitory activities, we examined inhibitory effects of 1 and 2 on compound 48/80-induced histamine release from rat peritoneal mast cells. As shown in Table 3, the inhibitory activities of 1 and 2 were superior to that of SCG.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] It was suggested that these substances may be useful ingredients of hair-care cosmetics for prevention of gray hair and alopecia. As a part of our continuous study on P. nigrum leaf, we examined anti-allergic effect of the leaf, because hair care cosmetics having anti-allergic activity may be desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…nigrum and fruit of P . cubeba revealed strong inhibiting activity in the concentration of 2 mg/ml [11].…”
Section: Plant Raw Materialsmentioning
confidence: 95%
“…Moreover, 5% solution of methanol extract from P . Nigrum leaves, applied locally during the in vivo test of hair growth in mice responsive to testosterone, revealed strong antiandrogenic properties [11].…”
Section: Plant Raw Materialsmentioning
confidence: 99%